2012
DOI: 10.1111/j.1365-2729.2012.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexic students in higher education and virtual learning environments: an exploratory study

Abstract: This paper presents the results of an interview‐based study of the use of virtual learning environments (VLEs) among dyslexic students. Interviews were carried out with 12 informants who had been formally diagnosed as dyslexic. The informants were either enrolled in a university or college programme, or had graduated less than a year before the interview. The findings reveal that dyslexic students experience a number of challenges associated with VLE use, including information overload, imperfect word processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
1
27
0
4
Order By: Relevance
“…Therefore, they claimed that such tools are not accessible for users with dyslexia. Similarly, Habib et al [33] found that users with dyslexia shun search functions of virtual learning environments which do not tolerate typological or spelling mistakes.…”
Section: Accessibility Of Resource Discovery Toolsmentioning
confidence: 99%
“…Therefore, they claimed that such tools are not accessible for users with dyslexia. Similarly, Habib et al [33] found that users with dyslexia shun search functions of virtual learning environments which do not tolerate typological or spelling mistakes.…”
Section: Accessibility Of Resource Discovery Toolsmentioning
confidence: 99%
“…Studies have also been conducted on accessibility of LMSs (Habib, et al, 2012;Woodfine, et al, 2008;Ulbricht, et al, 2012). Most of these studies focus on accessibility of one particular LMS in relation to users with specific disabilities, such as dyslexia (Habib, et al, 2012), hearing or visual impairments (Kyun, et al, 2007;Debevc, et al, 2012;Ulbricht, et al, 2012).…”
Section: Related Workmentioning
confidence: 99%
“…Most of these studies focus on accessibility of one particular LMS in relation to users with specific disabilities, such as dyslexia (Habib, et al, 2012), hearing or visual impairments (Kyun, et al, 2007;Debevc, et al, 2012;Ulbricht, et al, 2012). For example, Habib, et al, (2012) have targeted students with dyslexia in higher education and identified several challenges associated with the use of Fronter based on an in-depth interview of 11 informants. The challenges include information overload, imperfect word processing tools, inadequate search functions, and having to relate to more than one system at a time.…”
Section: Related Workmentioning
confidence: 99%
“…In e-readers it is possible to have a larger font of letters, fewer words per line, greater spacing between lines, and control of screen brightness. On the other hand, in a study on the use of virtual learning environments (AVAs) 23 , with dyslexic undergraduate students, some preference for paper text was identified through interviews. Some dyslexics preferred to read the text on paper because it was easier to mark the important passages.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the 21 related scientific articles 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][21][22][23][24][25] published between 2010 and 2015, some aspects regarding the use of ICTs applied to dyslexia were suggested: type and font size; more suitable color variations in the screens that favor reading; control in the time of execution of the activities; text-to-speech conversion to be able to listen to the read text itself; phonological and multisensory resources to stimulate phonological awareness and spelling, besides interactive multimedia instruments as well as more appropriate characteristics of technology.…”
Section: Literature Reviewmentioning
confidence: 99%